Commercial culture and inoculant additives for alfalfa and whole-plant corn silages - Hinds, M.; Bolsen, K.; Ilg, H.; Milliken, George A. (Kansas State University. Agricultural Experiment Station, 2010)
Experimental 5 gallon plastic silos were used in three trials to evaluate these alfalfa and corn silages: 1) control (no additive); 2) CULBAC® culture; 3) McNess ® inoculant; 4) SILA-GREEN® inoculant; and 5) Biomax SI ® inoculant. Two silos per treatment were opened on days 1, 2, 4, 7, 14, and 56 post-ensiling in trial 1 (alfalfa) and trial 2 (corn) and the changes that occurred during the ensiling process were compared by using nonlinear models. Only 56-day silages were evaluated in trial 3 (alfalfa). All silages were of acceptable quality. The four culture/inoculant additives had no consistent effects on 56-day end-product silages in the three trials or the ensiling dynamics in trials 1 and 2. Aerobic stability of corn silage was enhanced by the culture/inoculant treatments, while all 10 alfalfa silages were highly stable in air, regardless of treatment.
Keywords: Beef; Inoculant additives; Alfalfa; Corn silages; Silo